Performance Management Based on Key Performance Indicators (KPI) to improve Organizational Effectiveness - Kushariyadi, Kushariyadi; Wahid, Deden Abdul; Albashori, Muhammad Fatkhurohman; Rustiawan, Indra; ARDENNY, ARDENNY; Wahyudiyono, Wahyudiyono (PT. Anagata Sembagi Education, 2025)
This study aims to examine the relationships between Key Performance Indicators (KPI) Measurement, Employee Performance, and Organizational Effectiveness. The research employs multiple statistical analyses to assess the validity, reliability, and normality of the variables involved, as well as their impact on organizational outcomes. The results indicate a strong and statistically significant positive correlation between KPI Measurement (X1), Employee Performance (X2), and Organizational Effectiveness (Y), with all variables showing high reliability and normal distribution. Furthermore, the regression analysis reveals that 62.3% of the variation in Organizational Effectiveness is explained by KPI Measurement and Employee Performance. The findings suggest that both KPI Measurement and Employee Performance significantly contribute to improving Organizational Effectiveness, with each having a positive effect. These results emphasize the importance of performance management systems and employee performance in enhancing organizational outcomes. The study provides valuable insights for organizations aiming to improve their effectiveness through better KPI measurements and employee performance strategies.